Pedagogical dimension of sport in the light of its socio-cultural conditions - Kaźmierczak, Arkadiusz (Journal of Education, Health and Sport, 2018)
The contemporary existence of sport in social discourse is not limited only to the area of sports competition, results and records or stadiums, which are the arena of struggle for athletes. Identified as a form of the individual’s search for its existence and the way of exceeding human potential, it has become the subject of constant reflection and research inspiration. Perceived as an interdisciplinary phenomenon with a rich axiological potential in many scientific studies, it is identified as a field of cultural, social, economic, recreational, political, ecological and educational scope.